Biogeografía de hongos micorrízicos arbusculares (HMA) en el cultivo de café (Coffea arabica L.) en la región San Martín, Perú - Medina Repoma, Victoria Elizabeth (2016)
In different Peruvian ecosystems, the roots of the vast majority of plants form symbiosis with AMF and is a key component to the efficient functioning of their host. Unfortunately it's not know biogeography of these fungi communities in different ecosystems of the country. Research about the diversity of AMF, its role in the ecosystem and the factors affecting them is disregarded. Also the identification native species of AMF and their geographical distribution is the initial step to generate technologies based on the use of these fungi. In this sense, this study was focused in to know biogeography of AMF in the cultivation of caturra coffee variety, in the localities of Aviation (Lamas), Buena Vista (El Dorado) and Los Angeles (Moyobamba). It was determined extraradical length mycelium, the percentage of colonization, the number of spores and the respective identification to species level. For this it was used the complete random design with 6 treatments and significance level of p<0,05. The results show a greater length of extraradical mycelium (43,64 cm / g soil) and greater number of spores (158 spores / 10 g of dry soil) in the dry season (August - September 2015); while the highest percentage of colonization (17,86%) was shown in the wet season (February - March 2016). Lamas province also had higher averages extra radical mycelium (39,48 cm / g soil), colonization percentage (26,40%) and spore density (167 spores / 10 g of dry soil). Finally they were identified 16 species of AMF-N, being Acaulospora and Glomus the most abundant